1999
DOI: 10.1046/j.1365-8711.1999.02896.x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of pulsations in the Am star HD 13079

Abstract: Pulsation in cool main‐sequence Am stars is a rare phenomenon observed in a few marginal Am stars and only one classical Am star. The chemically peculiar star HD 13079 is shown to be pulsating with a 78‐min period and a peak‐to‐peak B amplitude of 0.02 mag. The Hipparcos parallax, uvbyβ photometry and pulsations together suggest that HD 13079 is an Am star near the zero‐age main sequence, and that it is a fundamental‐mode pulsator on the red edge of the instability strip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…During the survey the CP stars HD 13038, HD 13079, HD 98851 and HD 102480 have been discovered to be new δ Sct pulsating variables, while HD 12098 has been discovered to be a rapidly oscillating Ap star. The pulsation properties of HD 13038 (Martinez et al 1999a), HD 13079 (Martinez et al 1999b) and HD 12098 ) have been reported earlier while those of HD 98851 and HD 102480 are presented here. Joshi et al (2000) discovered two main periods of 75 and 150 min for HD 98851.…”
supporting
confidence: 64%
“…During the survey the CP stars HD 13038, HD 13079, HD 98851 and HD 102480 have been discovered to be new δ Sct pulsating variables, while HD 12098 has been discovered to be a rapidly oscillating Ap star. The pulsation properties of HD 13038 (Martinez et al 1999a), HD 13079 (Martinez et al 1999b) and HD 12098 ) have been reported earlier while those of HD 98851 and HD 102480 are presented here. Joshi et al (2000) discovered two main periods of 75 and 150 min for HD 98851.…”
supporting
confidence: 64%
“…The original frequency solution for HIP44166 had f 2 1X348 d 21 Y but examination of the spectrum over a wider frequency range showed this to be an artefact induced by the peak at 12.6 d 21 . This probable d Scuti star may be of interest due to its spectroscopic classification as an Am star (see, e.g., Martinez et al 1999).…”
Section: A and F Starsmentioning
confidence: 99%
“…Indeed, pulsations of the δ-Scuti type 1 have been seen in many Am stars (e.g. Kurtz 1989;Martinez et al 1999;Kurtz & Martinez 2000;Joshi et al 2003;González et al 2008), but our understanding of the physics of pulsating Am stars is still far from being complete. Theoretical models can for instance partially explain that evolved Am stars can pulsate (κ-mechanism in He ii can drive the pulsations in evolved Am stars) and that marginal Am stars can be low-amplitude δ-Scuti stars (a sufficient amount of He remains to drive low-amplitude oscillations).…”
Section: Introductionmentioning
confidence: 99%